Building equity in addiction: is there potential for higher returns from stocks with products and services associated with addiction? - Tully, Sean Patrick, author; Vasudevan, Ramaa, advisor; Turtle, Harry, committee member; Mushinski, David, committee member (Colorado State University. Libraries, 2023)
Industries associated with addiction have long been some of the most profitable businesses on the planet. In both good times and bad, human beings seem to be drawn to activities – whether having a drink, smoking a cigarette, or venturing to the local casino – that fall into the category of vice and have a history of being associated with addiction. An individual going through tough times may be sitting in their apartment drinking the same scotch as persons celebrating a colleagues' promotion in the pub across the street. Merriam-Webster defines vice as 'a moral depravity or corruption, a moral fault or failing, or a habitual and usually trivial defect or shortcoming' (Merriam-Webster, 2020). As societal norms become more relaxed with time, some activities previously considered to be controversial, reflective of bad habits, or provided with the risk of developing a dependency are becoming more tolerated. In some cases, even previously illegal products are becoming legalized. This gives some companies with products and services considered potentially addictive in nature the opportunity to enter new markets and yield potentially higher returns for investors, albeit at the cost of promoting and providing the means to participate in socially harmful activities. What level of possible investment returns can investors taking equity in alcohol, tobacco, gambling, and cannabis companies expect? As far back as 2001, a report commissioned by Credit Suisse First Boston found that vice as a market sector outperformed the market as a whole and held up particularly well during past recession periods. If investing in companies associated with addiction and vice has produced attractive market returns for investors in the past, will a portfolio of investments in stocks specifically offering potentially addictive products and services produce similar results? Can investors taking equity in companies associated with potentially addictive products such as alcohol, tobacco, gambling, and cannabis expect higher returns versus investing in the S&P500 market index? The goal of this thesis is to explore whether investors can expect higher returns from investments associated with potentially addictive products and human vices when compared with returns of the broader market represented by the S&P500 index. We will construct an investment portfolio of stocks based on addictive products, and study how individual stocks in the portfolio correlate to overall market performance (betas vs benchmarks) by completing both equally weighted and market value-based analysis. We also perform regressions with the CAPM, Fama-French three-factor, and several control variable augmented models to analyze return performance of the addiction portfolio as compared to the S&P500.